Perancangan User Experience Aplikasi Pemantauan Kesehatan Ibu Hamil di POLINDES berbasis Mobile menggunakan Metode Human Centered Design (HCD) - Masgata Nafi'ul Kalam; Riswan Septriayadi Sianturi; Agi Putra Kharisma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
The Maternal Mortality Rate (MMR) because pregnancy in 2019 in the world is very high, at 303,000. Indonesia has the third highest MMR in 2017 with 177 deaths/100,000 births. Village Maternity Boarding School (POLINDES) participates reducing MMR because pregnancy. The results of interviews with pregnant women and midwives found problems at POLINDES are pregnancy data collection still manual, consultation must be in place, access to health information or the presence of a midwife is difficult to reach. The purpose of this research was to design a user experience application for pregnant women's health monitoring at POLINDES to facilitate online services between pregnant women and midwives. The user experience research method uses Human-Centered Design with the stages of literature study, user context analysis, user needs analysis, solution design, and solution design evaluation. This research produces wireframes, mockups, and prototypes, then tests using usability testing. Usability testing was conducted on 5 pregnant women and 5 midwives. The results of testing for pregnant women, the effectiveness aspect is 88,23%, the efficiency aspect is 0,139 goals/sec, and the satisfaction aspect is 85 in Excellent category with grade scale B. The test results for midwive, the effectiveness aspect is 90,62%, the efficiency aspect is 0,087 goals/sec, and the satisfaction aspect is 70,5 in Good category with grade scale C.